Farming systems research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Planned change in farming systems: progress in on-farm research edited by R Tripp 1991 348pp lSBN 0471 93417 8 hbk UKL39.95 John Wiley & Sons Ltd, Baffin Lane, Chichester, West Sussex PO19 1UD UK